Inquisitionis Hispanicae artes - González de Montes, R. active 16th century. (Heterodoxia Iberica, 2018)
The Inquisitionis Hispanicae Artes (Heidelberg, 1567), written by exiled Spanish Protestants, is the first systematic denunciation of the Spanish Inquisition. Its first part is a description of the Inquisition's methods, making use of the Inquisition's own instruction manual, which was not publicly known. Its second section presents a gallery of individuals who suffered persecution in Seville during the anti-Protestant repression (1557-1565). The book had a great impact, being almost immediately translated into English, French, Dutch, German, and Hungarian. The portraits very soon passed into Protestant martyrologies, and the most shocking descriptions (torture, auto de fe) became ammunition for anti-Spanish literature. This critical edition presents a new text as well as, for the first time, extensive notes.